2016
DOI: 10.3892/ol.2016.5387
|View full text |Cite
|
Sign up to set email alerts
|

Isoimperatorin induces apoptosis of the SGC-7901 human gastric cancer cell line via the mitochondria-mediated pathway

Abstract: Abstract. The present study was designed to investigate the antiproliferative activity of isoimperatorin against SGC-7901 cells and to examine the possible mechanisms. The antiproliferative activity of isoimperatorin against SGC-7901 cells was evaluated using an MTT assay, and the mechanisms were investigated using flow cytometry and western blot assays, which were used to determine the apoptotic rate and expression levels of mitochondria-mediated apoptosis-associated proteins, including Survivin, myeloid leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…This compound is present in Angelica dahurica, Notopterygium incisum, Ferula lutea, Angelica pubescens, and Peucedanum praeruptorum. Isoimperatorin exhibits various pharmacological activities, including antioxidant [255,256], anti-inflammatory [257], analgesic [258], antibacterial [259,260], and anticancer properties [261,262]. Wijerathne et al reported that isoimperatorin protected against OA-induced asthma via mitigation of airway inflammation and mucus hypersecretion evidenced by the decreased IL-4, IL-5, and IL-13 production [257].…”
Section: Fraxin Fraxin (7-hydroxy-6-methoxy-8-[(2s3r4s5s 6rmentioning
confidence: 99%
“…This compound is present in Angelica dahurica, Notopterygium incisum, Ferula lutea, Angelica pubescens, and Peucedanum praeruptorum. Isoimperatorin exhibits various pharmacological activities, including antioxidant [255,256], anti-inflammatory [257], analgesic [258], antibacterial [259,260], and anticancer properties [261,262]. Wijerathne et al reported that isoimperatorin protected against OA-induced asthma via mitigation of airway inflammation and mucus hypersecretion evidenced by the decreased IL-4, IL-5, and IL-13 production [257].…”
Section: Fraxin Fraxin (7-hydroxy-6-methoxy-8-[(2s3r4s5s 6rmentioning
confidence: 99%
“…However, significant future research will be needed on related fields in order to better develop the use of traditional Chinese medicines. e previous studies have shown that isoimperatorin effectively inhibits the proliferation of gastric cancer and induces its apoptosis [8][9][10]. Wang Meng [21] also confirmed that isoimperatorin has obvious antitumor activity.…”
Section: Discussionmentioning
confidence: 93%
“…It has been found in the previous studies that isoimperatorin has a wide range of pharmacological effects as follows: can promote the differentiation of adipocytes; may prevent diabetes [1]; inhibits the activity of melanocytes; promotes the expression of melanin transport related protein Rab27a; reduces the melanocyte melanin content [2,3]; reduces the expression of nitric oxide and tumor necrosis factor-α (TNFα) in fibroblast synovial cells [4]; improves the mitochondrial function; protects the acute liver injury induced by carbon tetrachloride [5]; relaxes the blood vessels [6]; and increases the breast cancer cell radiotherapy sensitivity [7]. Besides, isoimperatorin has anti-inflammatory, analgesic, and antitumor effects and can induce apoptosis as well as inhibit the proliferation of gastric cancer cells [8][9][10]. To date, no reports have examined whether isoimperatorin has an antitumor effect on nasopharyngeal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The BGC823 cells (5 × 10 5 cells/well) were seeded in 12-well plates for 24 h and treated with PA (0, 10, 20 or 40 μg/mL) for 48 h, followed by harvesting and washing (thrice) in chilled PBS, and staining with Annexin V-FITC/PI. The stained cells were then subjected to flow cytometric analysis using FACSCalibur from BD Biosciences (San Jose, CA, USA) [16].…”
Section: Cell Apoptosis Assaymentioning
confidence: 99%